Effects of Screw Speed on Screw Pressure and Temperature: A Case of Non-Newtonian Non-Isothermal Flow - Amos Maina; Fredrick Mwema; Abiodun Bayode; Lungile Nyanga (Engineering proceedings, 2025)
This study uses ANSYS Polyflow to analyze the relationship between speed, temperature, and pressure. A wheat flour’s viscosity, thermal conductivity, and heat capacity were found to be 12,000 cps, 0.375 W/m-K, and 2190 J/kg-K, respectively. The speed was increased from 5 to 100 RPM in five-step increments. The findings of pressure and temperature measurements were examined for statistical significance, as well as the link between change in screw speed and change in pressure and temperature. As the screw speed increased, so did the pressure and temperature, with a maximum of 41 bar and 372 K recorded at 100 RPM. Proper screw speed selection is critical for maintaining optimal pressure and temperature conditions in the extruder, which ensures great product quality and operating efficiency.